2021
DOI: 10.1080/10803548.2020.1870836
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ergonomists’ experiences after participation in a theoretical and practical research project on observational risk assessment tools

Abstract: The aim of this qualitative study was to explore how ergonomists experienced an e-learning concept as a tool for knowledge translation; furthermore, to explore what, if any, impact the knowledge translation had regarding the ergonomists' work with risk assessments. Methods. Twelve Swedish ergonomists employed in the occupational health service (OHS) participated in a research project, which included an e-learning program in risk assessment training. Focus group interviews and individual interviews were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Thereafter, the start-up meeting, communication, collaboration and supportive management were facilitating factors that made the process flow smoothly. In an earlier study, ergonomists reported that a start-up meeting for planning exposure assessments is important for establishing a mutual framework for the assessment and establishing contacts with the stakeholders [47]. In the present study, it was revealed that the planning at the start-up meeting should include a role and responsibility structure, and that a process leader who has the overall responsibility for the process should be appointed.…”
Section: Discussionmentioning
confidence: 65%
“…Thereafter, the start-up meeting, communication, collaboration and supportive management were facilitating factors that made the process flow smoothly. In an earlier study, ergonomists reported that a start-up meeting for planning exposure assessments is important for establishing a mutual framework for the assessment and establishing contacts with the stakeholders [47]. In the present study, it was revealed that the planning at the start-up meeting should include a role and responsibility structure, and that a process leader who has the overall responsibility for the process should be appointed.…”
Section: Discussionmentioning
confidence: 65%
“…Initially, the ergonomists individually learned and trained on the six selected methods during a three-week period using an e-learning platform [ 50 ]. The training encompassed: (1) a pre-recorded lecture on general aspects of risk assessment, (2) pre-recorded instruction videos with “walk-through” examples where the six selected methods were applied on different work tasks and (3) self-supported training using a video library with film clips (two to six minutes long) of different work tasks.…”
Section: Methodsmentioning
confidence: 99%